Carbonized cellulose nanofibers as dielectric heat sources for microwave annealing 3D printed PLA composite. (1st March 2020) - Dong, Ju; Huang, Xingyan; Muley, Pranjali; Wu, Tongyao; Barekati-Goudarzi, Mohamad; Tang, Zhengjie; Li, Meichun; Lee, Sunyoung; Boldor, Dorin; Wu, Qinglin
Abstract: Filament fused fabrication (FFF) is an extrusion-based 3D printing technology for manufacturing thermoplastic components. One major obstacle facing 3D printed thermoplastic material is the reduced crystallinity resulting from a fast quench when material exiting the 3D printer hot nozzle solidifies quickly at the low-temperature platform, leading to weak mechanical performance. Here, we report an accelerated annealing strategy with the assistance of microwave heating, aiming to enhance crystallinity and mechanical performance of FFF 3D printed polylactic acid (PLA) composite. We selected naturally abundant cellulose fibers as precursors for producing carbonized cellulose nanofibers (CCNFs), and compounded CCNFs with PLA to produce bi-component filament for 3D printing final composite. After being irradiated with microwave, the embedded CCNFs in composite selectively absorbed microwave energy and generated heat. Subsequently, the localized heat transferred to the adjacent PLA regions, triggering amorphous PLA chains to repack and convert to new crystallites. In this work, annealing conditions, including heating method (i.e., oven annealing vs. microwave annealing), time (0–120 min), and temperature (80 vs. 120 °C), were systematically studied to understand the relevant effects on the resulting parameters including composite crystallinity and tensile strength. Microwave annealing method was also compared with conventional oven annealing method and results shows that microwave annealing significantly reduced the required annealing time to reach the maximum crystallinity and tensile strength. Notably, microwave annealing performed below cold crystallization temperature was exceptionally suitable to develop an optimized crystallinity and tensile strength for 3D printed PLA composite. Graphical abstract: Image 1